THE IMPLEMENTATION INTERNAL CONTROL SYSTEM GOVERNMENT WITH GOVERNMENT REGULATION RELEASE OF NO. 60/2008 IN KPU JEMBER REGENCY: A PHENOMENOLOGY APPROACH: SPIP - SUKMA ULI NUHA SUGIYONO; Muhammad Miqdad Miqdad; Agung Budi Sulistiyo Sulistiyo (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2021)
According to the Government Regulation of the Republic of Indonesia Number 60 of 2008 concerning the Government's Internal Control System, SPIP is an internal control system that is carried out thoroughly within the Central Government and Regional Governments. The important role of the SPIP is expected to create a culture of supervision over all activities in the entity so that early on it can detect the possibility of storage and minimize the occurrence of actions that can harm the state. SPIP which consists of elements of the Control Environment, Risk Assessment, Control Activities, Information and Communication, and Control Monitoring.The work of the KPU, both in Jember and other regions, is a phased work, which focuses on elections at both the central and regional levels so that the focus of work at this stage is that at this time SPIP reporting is only for administrative purposes. This is the reason why the author describes the phenomena that exist in the field, with the hope that in the future it will not only be an administrative complement but can be used as a control to increase the effectiveness of management at the Jember Regency KPU and can implement SPIP on an ongoing basis. The type of research used is qualitative research using a phenomenological study approach, because the author wants to describe the implementation of SPIP in Jember Regency KPU.